ANALYSIS OF GENE TARGETING EVENTS IN BUCKWHEAT (Fagopyrum esculentum) TRANSFORMED b THE MUTANT STRAINS OF Agrobacterium tumefaciens THAT HAVE DEFICIENCY IN T-??DNA INTEGRATION STEP INTO PLANT GENOME - Kojima, Mineo; Suparthana, Putu; Shimizu, Tsutomu; Nogawa, Masahiro (International Journal of Biosciences and Biotechnology; Vol 2 No 1 (2014))
Gene targeting events were analyzed in buckwheat (Fagopyrum esculentum, var. Shinano No. 1) that werein planta transformed (T1) by the three strains of Agrobacterium tumefaciens harboring a gene targetingvector for an endogenous gene (acc.no.AB327276); M-??1 mutant (abvA::Tn5) and M-??31 mutant (virA::Tn5)strains, both of which are capable of transferring its T-??DNA into nucleus of host plant cell, but have adeficiency in T-??DNA integration step into chromosome and LBA4404 strain, being a commonly usedstrain. The results of both phenotype examination and Southern blot analysis implied that a targetingconstruct(s) was integrated into a different locus (loci) each depending on the strain of A. tumefaciens usedfor transformation. Both 5’-??end and 3’-??end flanking DNA segments that were expected from preciseinsertion of targeting construct into the endogenous U-??gene locus were obtained by PCR with 3 (23%)transformants out of the randomly selected 13 transformants by M-??1 mutant strain, while only 3’-??endflanking DNA segment was obtained with 3(21%) transformants out of 14 transformants by M-??31 strain.Taken together, the results suggested the potential of usage of a mutant strain of A. tumefaciens for genetargeting which has a deficiency in T-??DNA integration step into plant genome.
Keywords: Agrobacterium tumefaciens, gene targeting, buckwheat, Fagopyrum esculentum, mutant strains of A. tumefaciens